Prevalence of Depression Among Staff at the City Institute for Emergency Medical Services Belgrade (Engrami, 2022)
Introduction: According to the WHO, depression is a common mental disorder where workplace conditions play a significant contributing factor.Objective: To examine the prevalence of depression and the relationship with sociodemographic characteristics in staff at the Institute for Emergency Medical Services (EMS) Belgrade, i.e., physicians, medical technicians, drivers and administrative workers.Methodology: The research was conducted at the City Institute for EMS Belgrade in the period from December 1 to December 6, 2007. The questionnaire consisted of questions about the sociodemographic characteristics of participants, a self-assessment questionnaire for depression PHQ-9 and a question about the use of antidepressants. The data that was collected was statistically processed with the software package SPSS 20.0Results: The study included 118 participants, 58.47% were male and the average age was 40.77 ± 8.86. The result of the PHQ-9 test showed that 30% of the participants had subsyndromal depression, 11% had a mild depressive episode, most often in female participants (p = 0.023) and in administrative workers (p = 0.003). Depression was present in 16.95% of respondents. Out of the 9 listed symptoms of depression, fatigue/extreme exhaustion were most commonly present (47.46%) as well as feelings of emptiness and hopelessness (43.22%). Only 11.86% of participants used antidepressants and there was no statistically significant difference in relation to the observed parameters.Conclusion: Subsyndromal depression is significantly present among the EMS staff in Belgrade, more often among female participants and those working in administration.
Keywords: depression; Emergency Medical System; PHQ-9 test